Design and implementation of multi-grooved simultaneous separation and screening equipment - Shizhou Lu; Yuankai Ren; Xiran Wang; Xuguang Dong (The Journal of Engineering, 2019)
The separating and screening of cylindrical parts are always difficult in the assembly industry, and the previous devices have the weakness of low working efficiency, low accuracy, and low automaticity. Based on the theoretical analysis, modelling and simulation, a theory of simultaneous separation and equidistant screening is proposed, and the corresponding equipment is established with the core modules of the multi-grooved cylindrical cam mechanism, pneumatic system, sensing, and controlling system. Solidworks software is used for three-dimensional modelling and kinematic simulation, which verify the correctness of the equipment design.